Pengaruh Akupresur pada Titik Zhongwan (CV12) untuk Meningkatkan Nafsu Makan Balita - Sari, Dewi Kartika; Anggraeni, Enggar (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Decreased appetite in toddlers is a significant risk factor for malnutrition and stunting. Acupressure at the Zhongwan (CV12) point, a component of Traditional Chinese Medicine, is known to enhance digestive function and stimulate appetite. This study aims to determine the effect of acupressure at the CV12 point on improving toddlers’ appetite. A pre-experimental one-group pre-post test design was used, involving 32 toddlers aged 1–5 years with decreased appetite who underwent six sessions of acupressure therapy. The results of the McNemar test showed a significant improvement in appetite following the intervention (p = 0.000). Before the intervention, 68.8% of the children had poor appetite, which improved to 90.6% having good appetite post-intervention. These findings indicate that acupressure at the Zhongwan (CV12) point is an effective non-pharmacological method to improve toddlers’ appetite, potentially contributing to stunting prevention.